Tromboprofilaxis para prevenir tromboembolismo venoso en pacientes posquirúrgicos. - Ygnacio-Mestanza, J.C. (2024)
Venous thromboembolism (VTE) is an important cause of morbidity and mortality with a cardiovascular factor. Its appearance is generally determined by risk factors such as surgery. This occurrence can be avoided in some scenarios thanks to the administration of thromboprophylaxis. Therefore, the objective of the study was to analyze the effectiveness of thromboprophylaxis on the incidence of VTE in post-surgical patients. The study was developed thanks to an analytical approach to information, with the PRISMA methodology of systematic reviews, for which works were retrieved through the PUBMED, Science Direct and Scopus search engines, where 20 academic documents were recognized. It is concluded that thromboprophylaxis reduces the incidence of VTE in post-surgical patients; however, it is recommended to continue with studies to determine the most specific anticoagulant according to the type of surgery.